Podocyte Activation of NLRP3 Inflammasomes Contributes to the Development of Proteinuria in Lupus Nephritis - Fu, Rong; Guo, Chaohuan; Wang, Shuang; Huang, Yuefang; Jin, Ou; Hu, Haoqiang; Chen, Jingxian; Xu, Bihua; Zhou, Mianjing; Zhao, Jijun; Sung, Sun‐sang J.; Wang, Hongyang; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2017)
Objective Development of proteinuria in lupus nephritis (LN) is associated with podocyte dysfunction. The NLRP3 inflammasome has been implicated in the pathogenesis of LN. The purpose of this study was to investigate whether NLRP3 inflammasome activation is involved in the development of podocyte injury in LN. Methods A fluorescence‐labeled caspase 1 inhibitor probe was used to detect the activation of NLRP3 inflammasomes in podocytes derived from lupus‐prone NZM2328 mice and from renal biopsy tissues obtained from patients with LN. MCC950, a selective inhibitor of NLRP3, was used to treat NZM2328 mice. Proteinuria, podocyte ultrastructure, and renal pathology were evaluated. In vitro, sera from diseased NZM2328 mice were used to stimulate a podocyte cell line, and the cells were analyzed by flow cytometry. Results NLRP3 inflammasomes were activated in podocytes from lupus‐prone mice and from patients with LN. Inhibition of NLRP3 with MCC950 ameliorated proteinuria, renal histologic lesions, and podocyte foot process effacement in lupus‐prone mice. In vitro, sera from diseased NZM2328 mice activated NLRP3 inflammasomes in the podocyte cell line through the production of reactive oxygen species. Conclusion NLRP3 inflammasomes were activated in podocytes from lupus‐prone mice and from LN patients. Activation of NLRP3 is involved in the pathogenesis of podocyte injuries and the development of proteinuria in LN.